Management and Prevention of Nasal Schistosomosis in a She-Buffalo: Clinical Insights - Vutharamalluru, Gnani Charitha; Pathalota, Gayathri; Badvel, Surendra; Pothanaboina, Guru Vishnu; N, Jagadeeswar Reddy (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Nasal schistosomosis (Snoring disease) is a snail born trematode infection of domestic and wild ruminants  caused by Schistosoma nasale (Chandra Sekhar et al., 2021).  This pathogen primarily affects cattle and buffaloes leading  to significant economic losses in livestock dependent areas  across Asia and Africa. Serious outbreaks of this disease  among cattle and buffaloes have been reported in certain  regions of India, viz., Tamil Nadu, Karnataka, Kerala, West  Bengal (Sumanth et al., 2004; Agarwal, 2012; Ravindran  and Kumar, 2012). Fresh water snail belonging to genus  Indoplanorbis acts as intermediate host (Liu, 2010). Primary  mode of transmission is through skin penetration when free  swimming larval stage cercaria comes in contact with the  ruminants in contaminated water bodies. Upon entering  the definitive host, the parasite primarily affects nasal blood  vessels. The main pathogenic effects are associated with the  eggs that trigger granuloma formation through release of  antigens that stimulate the host immune system, leading to  a chronic inflammatory response in the nasal mucosa that  may occlude the nasal passage.
Keywords: Bovine Nasal schistosomosis, Schistosoma nasale, Boomerang shaped egg, Miracidium, Anthiomaline, Successful management